COVID-19 Pandemic and the Adoption of E-Learning as Alternative Teaching and Learning: Perspectives of Tertiary Students - Yaw Odame Gyau; Ebenezer Malcalm (Noyam Journals, 2023)
This study investigated the perceptions, attitudes, and challenges of students towards the adoption of e-learning as an alternative teaching and learning approach during the onslaught of the COVID-19 pandemic, in the case of the Ghana Institute of Journalism (GIJ) and the Ghana Communication Technology University (GCTU). The purpose of the study was to investigate and examine perceptions, attitudes, and challenges of students in the adoption of e-learning as alternative teaching and learning during the pandemic. The study adopted a purposive and random stratified sampling technique to respond to hypothetical issues; that there is a significant relationship between students' perceptions, attitudes and challenges and the adoption of e-learning in the COVID-19 crisis. From the perspective of the students, findings include a lack of data bundles, online learning being difficult and the unpreparedness of the institutions to adopt e-learning within the first four weeks of the pandemic. The adoption of e-learning as alternative learning in Tertiary institutions, in the wake of the COVID-19 pandemic, is quite novel and still evolving and educational institutions are quite far from absolute transformation.